A Systematic Review of Challenges Experienced by Cross Border Investments in Developing Countries. A Case of Multinational Companies Expanding into the African Region E - Katoma, Tatenda; Qutieshat, Abubaker (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This paper provides a systematic review of challenges faced by multinational companies in developing countries, in particular the African region. Design/methodology/approach: This paper review relevant literature aimed at addressing the research question: “What are the challenges faced by cross border investments as they expand into Africa? The paper discusses the findings and proposes various recommendations to the challenges with the aim of improving the investment environment in developing countries to boost economic activity. Findings: Major challenges identified to be impacting cross border investments in developing countries are Political environment, regulatory environment, diversity and multicultural challenges, Leadership, Governance and Economic environment. For the purposes of literature review, the term cross border investments may be interchanged with Multinational Companies. The paper concludes by highlighting areas for future research. Paper type: Review Paper